PERENCANAAN DAN PENGEMBANGAN GOA COKRO BERBASIS KONSERVASI SEBAGAI PENUNJANG DAYA TARIK WISATA DI DESA UMBULREJO KECAMATAN PONJONG KABUPATEN GUNUNGKIDUL - , SETIA PAMBUDI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tourism can be support for growth evolution of evolve countries. Indonesia is one of evolve countrie that can maximize their potential to develop tourism for growing economy in the country. And now some people like natural attractions include the special interest tourism, adenture, experiences and knowledge. Gunungkidul is one area in Yogyakarta region that has many natural attractions. One of them was developed that the cave is located in Blimbing Hamlet, Umbulrejo Village, Ponjong District. Gunungkidul.Region. Cokro cave is also called Luweng Cokro because of its shape approximately 18 m vertically into the ground, distance of this cave about 50 m to the west and 200 m to the east. This research is about planning and development based conservation in Cokro cave. The empowerment of potential is not miaximized like the animals or the ground in Blimbing Hamlet where itâs possible to develop and can be a very big result for local government and communities.